2019
DOI: 10.1128/aac.01163-19
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Blockade and TLR7 Activation Lack Therapeutic Benefit in Chronic Simian Immunodeficiency Virus-Infected Macaques on Antiretroviral Therapy

Abstract: Antiretroviral therapy (ART) limits human immunodeficiency virus 1 (HIV-1) replication but does not eliminate the long-lived reservoir established shortly after viral acquisition. A successful HIV cure intervention necessitates either elimination or generation of long-term immune control of the persistent viral reservoir. Immune modulating strategies in conjunction with ART hold promise for achieving cure by inducing viral antigen expression and augmenting infected cell killing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 46 publications
(53 reference statements)
6
37
0
Order By: Relevance
“…We did observe several blips of viremia in treated RMs, but similar viral blips were also seen in the control group around the same timepoints indicating that this transient viremia was likely unrelated to GS-986 treatment (Fig 1B and 1C). Our findings conflict with Lim et al [30], but are consistent with reports by Del Prete et al, and Borducchi et al, and Bekerman et al [18,[31][32][33]. Based on the safe induction of innate immune activation we observed in infants, TLR-7 agonists remain promising for use as vaccine adjuvants or perhaps could be explored in combination with other agents to stimulate virus reactivation from latency.…”
Section: Plos Pathogenssupporting
confidence: 87%
“…We did observe several blips of viremia in treated RMs, but similar viral blips were also seen in the control group around the same timepoints indicating that this transient viremia was likely unrelated to GS-986 treatment (Fig 1B and 1C). Our findings conflict with Lim et al [30], but are consistent with reports by Del Prete et al, and Borducchi et al, and Bekerman et al [18,[31][32][33]. Based on the safe induction of innate immune activation we observed in infants, TLR-7 agonists remain promising for use as vaccine adjuvants or perhaps could be explored in combination with other agents to stimulate virus reactivation from latency.…”
Section: Plos Pathogenssupporting
confidence: 87%
“…Accordingly, several clinical studies from our group have demonstrated HIV-1 (re)activation through an IFNα-α induced CD4+ Tcell activation and increased HIV-1-specific polyfunctionality of CD8+ T cells following TLR9 stimulation (74,75,92). Similar effects have been demonstrated ex vivo and in vivo in TL7TLR7 agonist studies (51,93,94).…”
Section: Immunomodulatory Properties Of Tlr Agonistssupporting
confidence: 60%
“…Bekerman et al tested the immunomodulatory effect of a chimeric anti-PD-1 antibody and the TLR7 agonist GS-9620 in chronically SIV infected rhesus macaques (94). In a four-arm controlled design, NHPs received 0.15 mg/kg GS-9620 by oral gavage every other week for a total of 10 administrations, alone or in combination with 10 mg/kg anti-PD-1 antibody.…”
Section: Tlr Agonists and Programmed Death-1 (Pd-1) Inhibitionmentioning
confidence: 99%
“…However, a key distinction is that in cancer the self-immunogen is pervasive; whereas, in ART-treated HIV infection chronic antigenic stimulation arises largely from gut microbial translocation, not from viral proteins. This different in antigen source may represent a key obstacle when translating therapies between cancer and HIV models (63). In designing immunotherapy strategies, it is also important to consider that adverse event outcomes between these models have substantially different tolerances, as HIV is a manageable chronic disease and cancers are invariably fatal.…”
Section: Discussionmentioning
confidence: 99%